2008
DOI: 10.2353/ajpath.2008.080006
|View full text |Cite|
|
Sign up to set email alerts
|

Soluble Forms of the Notch Ligands Delta1 and Jagged1 Promote in Vivo Tumorigenicity in NIH3T3 Fibroblasts with Distinct Phenotypes

Abstract: We previously found that soluble forms of the Notch ligands Jagged1 and Delta1 induced fibroblast growth factor receptor-dependent cell transformation in NIH3T3 fibroblasts. However, the phenotypes of these lines differed, indicating distinct functional differences among these Notch ligands. In the present study, we used allografts to test the hypothesis that NIH3T3 fibroblasts that express soluble forms of Delta1 and Jagged1 accelerate tumorigenicity in vivo. With the exception of the full-length Jagged1 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
5
25
0
Order By: Relevance
“…The current work shows that Notch signaling has a critical role in modulating the cellular activity of Fbs, and activation of the Notch pathway aids to convert Fbs from 'tumor promoters' to 'negative regulators'. Our observations, thus, are consistent with earlier reports (Ishikawa et al, 2008;Urs et al, 2008) highlighting Notch signaling as a negative regulator in controlling the cellular activity of Fbs, and collectively provide a theoretic basis for practically targeting Notch signaling as a unique approach to modulate the functional phenotype of stromal Fbs in tumor tissue. On the other hand, Notch signaling is involved in regulating cellular behavior in a variety of cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current work shows that Notch signaling has a critical role in modulating the cellular activity of Fbs, and activation of the Notch pathway aids to convert Fbs from 'tumor promoters' to 'negative regulators'. Our observations, thus, are consistent with earlier reports (Ishikawa et al, 2008;Urs et al, 2008) highlighting Notch signaling as a negative regulator in controlling the cellular activity of Fbs, and collectively provide a theoretic basis for practically targeting Notch signaling as a unique approach to modulate the functional phenotype of stromal Fbs in tumor tissue. On the other hand, Notch signaling is involved in regulating cellular behavior in a variety of cells.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Notch pathway activation through either overexpression of the Notch1 intracellular domain (N IC ) or stabilization of N IC by ablation of Sel-10 (Fbxw7), a negative regulator of Notch signaling, resulted in cell-cycle arrest and apoptosis in mouse embryonic Fbs (Ishikawa et al, 2008). Consistently, inhibition of Notch signaling by soluble forms of the Delta-like-1 and Jagged1 ligands was able to induce Fb growth factor receptor-dependent transformation of NIH 3T3 Fbs in vitro (Urs et al, 2008). These studies pointed to Notch signaling having a negatively regulatory role in controlling the cellular behavior of Fbs and suggested that the cellular activity of Fbs can be regulated by manipulation of Notch signaling.…”
Section: Introductionmentioning
confidence: 91%
“…For example, overexpression of Jagged has been associated with poor prognosis, at least in breast cancer and prostate cancer (18), thus highlighting the importance of understanding its role in Notch signaling. Other recent studies have shown that Notch signaling can be activated by soluble forms of the ligands Jagged and Delta (19)(20)(21). The soluble Jagged and Delta have different effects on tumor progression--soluble Delta inhibits tumor growth (22,23), whereas soluble Jagged strongly aggravates the malignant progression of cancer.…”
mentioning
confidence: 99%
“…Interestingly, EGFL, Tsp2, and Lrp1 bind to both Notch and canonical Notch ligands. Although transmembrane ligands are the dominant biologically active canonical Notch ligands, the Jag1 extracellular domain can be shed by β-secretase 1 (BACE 1), 56 and can display specific biological activities as a soluble molecule, such as inducing FGF receptor-dependent cell transformation in NIH3T3 fibroblasts 57 and keratinocyte differentiation.…”
mentioning
confidence: 99%